2003
DOI: 10.2139/ssrn.419881
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Corporate Law: A Cross-Country Comparison

Abstract: An earlier draft of this Article was written as a background report for the Worldbank, WORLD DEVELOPMENT REPORT 2002: BUILDING INSTrrUTIONS FOR MARKErs (2001). Financial support from the World Bank is gratefully acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Third, and as a consequence of the previous point, there is a stronger reliance on bright-line laws to limit the role of the courts. Once a country adopts the bright-line approach to lawmaking, this can lead into a trap, as courts will not be challenged to develop legal procedures and methods to deal with new circumstances, thus retarding the development of efficiently adaptive legal systems (Pistor et al, 2002(Pistor et al, , 2003. By the same token, Common Law systems can be persistent, given the high social reputation of judges attracting talent to this profession and the role of jurisprudence allowing for a vibrant legal debate fostering legal innovation.…”
Section: The Historical Determinants Of Financial Developmentmentioning
confidence: 99%
“…Third, and as a consequence of the previous point, there is a stronger reliance on bright-line laws to limit the role of the courts. Once a country adopts the bright-line approach to lawmaking, this can lead into a trap, as courts will not be challenged to develop legal procedures and methods to deal with new circumstances, thus retarding the development of efficiently adaptive legal systems (Pistor et al, 2002(Pistor et al, , 2003. By the same token, Common Law systems can be persistent, given the high social reputation of judges attracting talent to this profession and the role of jurisprudence allowing for a vibrant legal debate fostering legal innovation.…”
Section: The Historical Determinants Of Financial Developmentmentioning
confidence: 99%
“…Thirdly, and relatedly, the presence of complementarities across institutions in a given national context limits the scope for the successful transplantation of particular institutions into other contexts, no matter how well they may have worked in their systems of origin (Pistor et al, 2003). We may call this the transplant hypothesis.…”
Section: Political Systemmentioning
confidence: 99%
“…Where this has been done, evidence has been found of a distinctive type of legal evolution in 'transplant systems'. Pistor et al (2003), studying the development of corporate law in a number of developed and developing economies, found that legal rules in systems of origin had changed to a substantially greater extent than those in transplant systems. The latter displayed two types of response: in some cases erratic changes, often involving the reversal of previous policies; and in other cases, very little change over long periods of time.…”
Section: B the Diffusion Of Legal Norms In 'Transplant' Systemsmentioning
confidence: 99%